Pakan Fermentasi untuk Ternak Sapi Berbasis Sumber daya Lokal di Kelompok Tani Ternak “Lembah telaga” Desa Gumantar, Kabupaten Lombok Utara, Propinsi Nusa Tenggara Barat - Ni Made Yudiastari; Asnawi Asnawi; Luh Suariani; I Nyoman Kaca; Yan Tonga; Ni Ketut Sri Rukmini; Ni Ketut Etty Suwitari; Ni Ketut Mardewi; I Gede Sutapa; I Gusti Ayu Dewi Seri Rejeki; Ni Made Ayu Gemuh Rasa Astiti; I Gusti Agus Maha Putra Sanjaya (Universitas Sebelas Maret, 2025)
Fermented Feed for Cattle Based on Local Resources in the “Lembah telaga” Livestock Farmers Group, Gumantar Village, North Lombok Regency, West Nusa Tenggara Province. Gumantar is a village located in Kayangan District, North Lombok Regency, West Nusa Tenggara Province, Indonesia. This village has agricultural and plantation potential with the main products being rice, corn, peanuts, cashews, coffee, cocoa, coconut, bananas, and other horticultural crops. The problem that is often encountered is the very limited availability of food in the dry season. This makes many breeders sell their livestock at low prices during the dry season. Another problem is farmers' low knowledge of storage and preservation technology for feed ingredients as feed in the dry season. In the rainy season, the available food is quite abundant. Therefore, it is necessary to provide training regarding animal feed storage and preservation technology. One method that is widely used and easy to do is making fermented feed. Fermentation is the process of changing organic materials into other, more useful materials with the help of microorganisms in a controlled manner. The aim of fermentation is to reduce anti-nutritional substances, increase digestibility, increase shelf life and increase selling value. The final fermentation product contains compounds that are simpler and easier to digest than the source material. After the implementation team provided outreach to partners, knowledge of the types of forage waste for feed increased from 40% to 80%. Increase in forage nutrition (protein) from 6.7% to 16.45%. The results of the activity showed that there was an increase in farmers' ability to make fermented feed, the fermented feed produced could be stored for 6 months and there was an increase in the nutritional value of the feed.